Analisis Pemangku Kepentingan Pengelolaan Sumber Daya Hutan di Kabupaten Jember: (Studi Kasus di Desa Tugusari Kabupaten Jember) - Nurhuda Candra Hidayat; Erna Setijaningrum; Sulikah Asmorowati (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
This study aims to analyze stakeholders in forest resource management in Tugusari Village, Bangsalsari District, Jember Regency. This research is motivated by the drastic reduction of critical land in Jember Regency, or in other words, there is success in forest conservation in the period 2011-2015. In answering the problem formulation and analyzing stakeholders using a stakeholder approach with Overseas Development Administration theory to identify stakeholders. Meanwhile, for the categorization and interrelation of stakeholders using Reed's theory. This study uses descriptive qualitative method. The results of this study have identified primary, secondary and key stakeholders. The primary stakeholders were LMDH Wana Makmur and the Tugusari Village Government. Secondary stakeholders are PHW Unit VII Bondowoso Jember working area. The key stakeholder is the public company Perhutani KPH Jember. Meanwhile, the stakeholder category consists of key players, contact setters, subjects, and crowds. The key category is the public company Perhutani KPH Jember. The contract setters, namely the Village Government. Subjects were LMDH Wana Makmur and Crowd, namely UPT PHW VII Bondowoso, Jember working area. While the interrelation between LMDH Wana Makmur stakeholders and the public company Perhutani KPH Jember went well because they often held coordination meetings and collaborative involvement. Thus it can be concluded that the success of forest resource management in Tugusari Village, Bangsalsari District Jember is due to the excellent interrelation of key players and subjects.